REDUCTION OF MMP USING OLEOPHILIC CHEMICALS - VOON , CHOON LIN (2015)
The objective ofthis thesis was to study the ability of oleophilic chemicals in lowering the minimum miscibility pressure (MMP) of carbon dioxide (CO2) - crude oil mixture in CO2 enhanced oil recovery. Theuseof oleophilic chemicals to reduce MMP is much preferable compared to reduction of IFT of water using surfactant due to the low cost of oleophilic chemicals and they are readily available. From literature review, three chemicals from three different functional groups were selected based on their polarity, oil solubility, low water solubility and cost. They were 1-butanol (alcohol group), 2- butanone (ketone group), and butyric acid (carboxylic acid). Dulang crude was chosen as the crude of choicedue to its easyavailability in Malaysia and absenceof asphaltene in the crude while enables slim tube tests to be conducted. Dulang were used to prove the effectiveness of oleophilic chemicals in MMP reduction and tests on other crudes can be conducted in future research. Pure CO2 (99.99%) was used so that impurities would not affect the results.